Analysis Of Parents' Role In Shaping Children's Social Character In Pinggang Village - Maria Selviani Dadik; Jemali, Maksimilianus; Eliterius Sennen (Jurnal Pendidikan dan Kebudayaan Missio, 2024)
This study explores the role of parents in shaping the social character of children in Pinggang Village, Cibal District, Manggarai Regency. It addresses concerns regarding instances of childhood aggression, a perceived lack of social character development among children, and limited parental awareness of the importance of fostering social character. Employing a qualitative descriptive research methodology, the study utilized direct observation of children's activities in Pinggang Village. The findings highlight the critical need for parental guidance and support in the development of children's social character. This includes modeling positive behavior, providing early childhood education, and instilling core values such as honesty, empathy, politeness, and responsibility